Cut - McCormick, Patricia, 1956- (Asheville, N.C. : Front Street, 2000)
While confined to a mental hospital, thirteen-year-old Callie slowly comes to understand some of the reasons behind her self-mutilation, and gradually starts to get better.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
6.0
Young Adult
Keywords: Emotional problems -- Fiction; Family problems -- Fiction; Psychiatric hospitals -- Fiction; Self-mutilation -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction; Psychiatric hospitals -- Fiction; Self-mutilation -- Fiction